INFORMATION ABOUT AUTHORS - Vilnensia, Acta Paedagogica (Acta Paedagogica Vilnensia, 2015)
ZITA ABRAMAVIČIŪTĖ – master of music; doctoral student of social science (education) at the Department of Social Work and Sociology, Lithuanian University of Educational Sciences; Junior Researcher of Science Center, Lihuanian Academy of Music and Theatre. Research interests: music therapy/music therapy in neurorehabiliation, social integration of people with disabilities. Address: 39 Studentu Str., LT-08106 Vilnius, Lithuania; e-mail address: zita.abramaviciute@gmail.comVILMANTĖ ALEKSIENĖ – doctor of social sciences (education), master’s degree in music therapy, associate professor at Department of Social Work and Sociology, Lithuanian University of Educational Sciences. Research interests: arts therapy / music therapy, social work / social pedagogy, supervision. Address: 39 Studentu Str., LT-08106 Vilnius, Lithuania; e-mail address: vilmante_aleksiene@yahoo.comVANDA ARAMAVIČIŪTĖ – habilitated doctor of social sciences (education), professor at the Department of Education, Vilnius University. Research interests: general educology, education and spiritual development of a personality, methodology of educational research. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: aramaviciute@gmail.comMARUTA AVOTINA – master of mathematics, employee in A. Liepas Correspondence Mathematics School; lecturer at the Faculty of Physics and Mathematics, University of Latvia. Research interests: modern elementary mathematics and mathematics didactics, difference equations. Address: 29 Zellu Str., LV-1002 Riga, Latvia; e-mail address: marutaavotina@inbox.lv.CRISTIANA BARBIERATO – doctoral student of social science (education) at the Department of Education,Vilnius University. Research interests: philosophy of education, pedagogical authority, educational relationship. Address: 1/9 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: cristiana.barbierato@fsf.vu.ltVALENTINA DAGIENĖ – doctor of physical sciences (mathematics), habilitation at social sciences (educology), professor at the Institute of Mathematics and Informatics, Vilnius University. Research interests: informatics (computing) education research, didactics of informatics, intelligent technologies for education, programming education, gamification. Address: 4 Akademijos Str., LT-08663 Vilnius; e-mail address: valentina.dagiene@mii.vu.ltELGA DRELINGA – master of education, lecturer at the Faculty of Education and Management, Daugavpils University. Research interests: formation of the mathematical concepts in pre-school, teaching mathematics in primary schools. Address: 13 Vienības Str., LV-5401 Daugavpils, Latvia; e-mail address: elga.drelinga@du.lvDANGUOLĖ GERVYTĖ – doctoral student of social science (education) at the Department of Education,Vilnius University. Research interests: school education, catholic education, paradigm of assumption education, moral education. Address: 1/9 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: danguole.gervyte@gmail.com VILMA GESEVIČIENĖ – doctor of social sciences (education), lecturer at Department of Mathematics, Faculty of Science and Technology Lithuanian University of Educational Sciences. Research interests: mathematics didactics. Address: 39 Studentų Str., LT-08106 Vilnius, Lithuania; e-mail address: vilma. geseviciene@leu.ltVAIRA KARKLINA – doctor of social sciences (education), lecturer at the Faculty of Science and Engineering, Liepaja University. Research interests: mathematics education. Address: 4 Valdemara Str., LV3400 Liepaja, Latvia; e-mail address:vaira.karklina@liepu.lvELFRĪDA KRASTIŅA – doctor of social sciences (education), professor at the Faculty of Education and Management, Daugavpils University. Research interests: mathematics methodology and personalization of learning, design of textbooks and methodological materials for primary school. Address: 13 Vienības Str., LV-5401 Daugavpils, Latvia; e-mail address: elfridak@inbox.lv.MADIS LEPIK – PhD, associated professor of mathematics education at the Department of Mathematics, Tallinn University. Research interests: mathematics teachers’ beliefs and professional development, textbook studies, and proof and proving. Address: Narva road 25, 10120 Tallinn, Estonia; e-mail addres: mlepik@tlu.eeEDMUNDAS MAZĖTIS – associate professor at the Department of Didactics of Mathematics and Informatics, Faculty of Mathematics and Informatics, Vilnius University. Research interests: mathematics didactics. Address: 24 Naugarduko Str., LT-03225, Vilnius; e-mail address: edmundas.mazetis@mif.vu.ltEIMANTAS PĖLIKIS – specialist at the Institute of Mathematics and Informatics, Vilnius University. Research interests: introductory programming education, education data analysis, gamification. Address: 4 Akademijos Str., LT-08663 Vilnius; e-mail address: eimantas.pelikis@gmail.comBIRUTĖ POCIŪTĖ – Doctor of Social Science ( Psychology), Associate Professor at the Department of General Psychology, Vilnius University. Research interests: cognitive psychology, career development and counselling, educational psychology. Address: Universiteto Str. 9/1, LT-01513 Vilnius; e-mal: birute.pociute@fsf.vu.ltRAMINTA SENIŪNAITĖ – master student at Department of General Psychology, Vilnius University. Research interests: cognitive psychology, family psychology. Address: Universiteto Str., 9/1, LT-01513 Vilnius; e-mail: raminta.seniunaite@gmail.comANITA SONDORE – doctor of mathematics, associate professor at the Faculty of Natural Sciences and Mathematics, Daugavpils University. Research interests: teaching probability theory at secondary school and university level. Address: 13 Vienības Str., Daugavpils, LV-5401, Latvia; e-mail: anita.sondore@du.lv.GABRIELĖ STUPURIENĖ – doctoral student (informatics engineering, technological sciences) at the Institute of Mathematics and Informatics, Vilnius University. Research interests: informatics (computing) education research, informatics concepts, constructionism. Address: 4 Akademijos Str., LT-08663 Vilnius; e-mail address: gabriele.stupuriene@mii.vu.ltAGNESE ŠUSTE – master of mathematics, employee in A. Liepa’s Correspondence Mathematics School, lecturer at the Physics and Mathematics Faculty, University of Latvia. Research interests: modern elementary mathematics and mathematics didactics, difference equations. Address: 29 Zellu Str., LV-1002 Riga, Latvia; e-mail address: agnese.suste@gmail.com